Echinatin inhibits the growth and metastasis of human osteosarcoma cells through Wnt/β-catenin and p38 signaling pathways - Qiuping Lu; Huakun Huang; Xiaoxuan Wang; Lijuan Luo; Haichao Xia; Lulu Zhang; Jingtao Xu; Yanran Huang; Xiaoji Luo; Jinyong Luo (Pharmacological Research, 2023)
Osteosarcoma (OS) is a highly aggressive malignant bone tumor that mainly occurs in adolescents. At present, chemotherapy is the most commonly used method in clinical practice to treat OS. However, due to drug resistance, toxicity and long-term side effects, chemotherapy can’t always provide sufficient benefits for OS patients, especially those with metastasis and recurrence. Natural products have long been an excellent source of anti-tumor drug development. In the current study, we evaluated the anti-OS activity of Echinatin (Ecn), a natural active component from the roots and rhizomes of licorice, and explored the possible mechanism. We found that Ecn inhibited the proliferation of human OS cells and blocked cell cycle at S phase. In addition, Ecn suppressed the migration and invasion, while induced the apoptosis of human OS cells. However, Ecn had less cytotoxicity against normal cells. Moreover, Ecn inhibited the xenograft tumor growth of OS cells in vivo. Mechanistically, Ecn inactivated Wnt/β-catenin signaling pathway while activated p38 signaling pathway. β-catenin over-expression and the p38 inhibitor SB203580 both attenuated the inhibitory effect of Ecn on OS cells. Notably, we demonstrated that Ecn exhibited synergistic inhibitory effect with cisplatin (DDP) on OS cells in vitro and in vivo. Therefore, our results suggest that Ecn may exert anti-OS effects at least partly through regulating Wnt/β-catenin and p38 signaling pathways. Most meaningfully, the results obtained suggest a potential strategy to improve the DDP-induced tumor-killing effect on OS cells by combining with Ecn.